Antidepressant-induced mania in panic disorder: a single-case study of clinical and functional connectivity characteristics - Kim, Byung-Hoon; Kim, Seung-Hyun; Han, Changsu; Jeong, Hyun-Ghang; Lee, Moon-Soo; Kim, Junhyung (Frontiers in Psychiatry, 2023)
Panic disorder (PD) is a common disorder, and the comorbidity of PD and bipolar disorder (BD) is prevalent. Antidepressant-induced mania can negatively affect the long-term course of patients with PD. However, there is no consensus on the clinical features that suggest mania risk in PD. We investigated the resting-state functional connectivity (rsFC) of the first-diagnosed patient with PD who developed mania during PD treatment before mania onset. This study was conducted on a single case from a prospective study involving 27 patients with PD and 30 healthy controls (HCs). During the prospective study, one patient progressed to mania (PD-manic group), whereas the remaining 26 patients with PD did not progress to mania (PD-NM group) after at least 4 months of follow-up. The amygdala-based rsFC of neuroimaging performed at baseline was compared between the PD-manic and PD-NM groups using seed-to-voxel analysis. The clusters revealed significant differences in seed-to-voxel analyses and both amygdala as the region of interest (ROI). Therefore, exploratory comparison using ROI-to-ROI analysis was performed for the PD-manic group and HCs and PD-NM and HCs. The PD-manic group presented with left amygdala-based hypoconnectivity in both default mode network and frontoparietal network-related clusters. The PD-manic group also revealed stronger amygdala-based rsFC in clusters related to visual processing. Additionally, ROI-to-ROI analysis revealed that significant clusters between PD-manic and PD-NM groups differed from HCs in the PD-manic group but not in the PD-NM group. This study presented altered amygdala-based rsFC reported in previous studies, which was observed in patients with PD before mania onset. Our results provide preliminary evidence for the future use of amygdala-based rsFC as a biomarker of BD. However, further studies with larger cohorts and more cases are required to confirm these findings.